THE RELATIONSHIP OF SPERM PRODUCTIVITY AND SEX ACTIVITY OF DIFFERENT GENOTYPE BREEDING BOARS BY ACTN1 AND FSHβ GENES - Gyria, V. M.; Metlitska, O. I.; Usachova, V. Ye.; Myronenko, O. I.; Slynko, V. G. (Scientific Progress & Innovations, 2020)
The article is devoted to the estimation of breeding boars’ genotypes according to the indices of sex activity and sperm productivity and identification of the desired ACTN1, FSHβ gene genotypes for further breeding work in the herd. The purpose of our research was to identify the relationship of breeding boars’ genetic structure by ACTN1, FSHβ genes and describe the effect of their polymorphism on the indices of sperm productivity and sex activity of boars belonging to different breeds. The analysis of sperm productivity by ACN1 gene showed that the AA genotype of boars had a larger ejaculate volume by 28.6 ml (11.8 %, P≤0.05) than BB genotype boars of the same age, but were inferior to AB genotype boars by 52.4 ml (19.3 %). It was found out that sperm productivity and sex activity of breeding boars as to FSHβ gene were ambivalent: boars of the Large White breed had a larger ejaculate volume (89.0–33.7 ml, or by 0.8–4.3 times), and breeding boars of Landrace breed, on the contrary, were inferior as to this index (114.5– 123.3 ml less, or by 51.5–57.7 %). The results are statistically highly reliable (p≤0.001). On the average as to the estimated boars, a significant difference was established between the genotypes concerning the sper- matozoon motility (p≤0.05). A statistically significant preference (P≤0.001) of heterotic boars of AB genotype, ACTN1 gene of the Large White breed, Landrace, and Durok breeds was revealed as to the indices of contact with phantom and erection by 42.5–55.4 sec., as well as ejaculation intensity by 0.082–0.313 sec., respectively, which is confirmed by higher indices (2.1–4.2). AccordIng to the FSHβ gene, the same tendency regardIng sex activity of the studied boars was confirmed. On the whole, the analysis of haplotypes of ACN1 and FSHβ genes has shown that the selection of boars for their libido and sperm productivity will be more effective in AVAA sub-gene, as compared with AVAV and AAAV genotypes, where there is an increase of ejaculate by 7.6–38.6 %, spermatozoon concentration – by 14.3–30.2 %, spermatozoon motility by 2.5– 4.6 %, and higher mating activity: by the contact of breeding boar with phantom and erection by 47.8– 79.2 %, and ejaculation intensity – by 5.0–14.5 %. To assess the productive qualities of breeding boars, a separate role has been noted for using sperm productivity and sex activity indices, which make it possible to carry out the objective estimation of boars’ breedIng value for determining their breedIng rating.